2009
DOI: 10.1007/s10964-009-9397-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Distress Among LGBT Youth: The Influence of Perceived Discrimination Based on Sexual Orientation

Abstract: The authors evaluated emotional distress among 9th-12th grade students, and examined whether the association between LGBT status and emotional distress was mediated by perceptions of having been treated badly or discriminated against because others thought they were gay or lesbian. Data come from a school-based survey in Boston, MA (n=1,032); 10% were LGBT, 58% were female, and age ranged from 13-19 years. About 45% were Black, 31% were Hispanic, and 14% were White. LGBT youth scored significantly higher on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
542
4
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 804 publications
(603 citation statements)
references
References 71 publications
39
542
4
18
Order By: Relevance
“…Previous research has found a relationship between disclosure of sexual minority orientation at work and perceived discrimination [31] and multiple studies on sexual minority youth show that they frequently experience discriminatory events in school settings due to their sexual orientation, particularly boys [13,32,33]. These two forms of institutional and interpersonal discrimination are significant problems for SMM, and the current study suggests that this may even be associated with intentions to engage in sexual behavior, again perhaps as a coping strategy.…”
Section: Heterosexism and Sexual Behavior In Smmsupporting
confidence: 47%
“…Previous research has found a relationship between disclosure of sexual minority orientation at work and perceived discrimination [31] and multiple studies on sexual minority youth show that they frequently experience discriminatory events in school settings due to their sexual orientation, particularly boys [13,32,33]. These two forms of institutional and interpersonal discrimination are significant problems for SMM, and the current study suggests that this may even be associated with intentions to engage in sexual behavior, again perhaps as a coping strategy.…”
Section: Heterosexism and Sexual Behavior In Smmsupporting
confidence: 47%
“…Sexual minority youth disproportionally experience mental health problems compared to heterosexual peers, including depressive symptoms (Almeida et al, 2009;Marshal et al, 2011) and higher rates of suicidal ideation and suicide attempts (Coker et al, 2010;Saewyc, 2011). For example, a meta-analysis documented that sexual minority youth were almost three times more likely than heterosexual youth to have attempted suicide .…”
Section: Introductionmentioning
confidence: 99%
“…Sexual minority adolescents are more likely than heterosexual peers to experience several types of violence, and to miss school because of fear Fedewa and Ahn, 2011). Studies have suggested that exposure to bullying and discrimination based on sexual orientation helps account for the link between minority orientation and adverse mental health outcomes (Almeida et al, 2009;Bontempo and D'Augelli, 2002;Williams et al, 2005). Thus, strategies to prevent mental health problems among sexual minority adolescents should include policies and programs that foster safe and supportive environments for youth of any orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, several studies focus on the experience of harassment and victimization (e.g., Almeida et al 2009). The last decades have seen notable attention to concerns for LGBT students; several of the articles included here focus on understanding and explaining the elevated rates of victimization and bullying that LGBT youth experience at school.…”
mentioning
confidence: 99%